Misi Gereja Menghadapi Pluralisme Agama: Antara Tantangan dan Peluang - Suriawan Suriawan (Pascasarjana IAKN Manado, 2023)
This research intends to conduct a literature study on the problem of pluralism which has an impact on missiology. The purpose of this study is to provide a map of the challenges and opportunities for the implementation of the church's mission in the context of religious diversity in Indonesia. This topic was then examined using a descriptive-analytical method with a qualitative approach. The recommendation from the results of this research is a new mission paradigm, namely by carrying out evangelization activities to present the mission of God's kingdom by: fighting for human values and the integrity of creation; bringing living testimonies that are increasingly real; and carry a gentle mission of reconciliation to embrace followers of other religions without trying to convert them to Christianity.